MicroRNAs as novel peripheral markers for suicidality in patients with major depressive disorder - Stapel, Britta; Xiao, Ke; Gorinski, Nataliya; Schmidt, Kevin; Pfanne, Angelika; Fiedler, Jan; Richter, Imke; Vollbrecht, Anna-Lena; Thum, Thomas; Kahl, Kai G.; Ponimaskin, Evgeni (Frontiers in Psychiatry, 2022)
Objective: Major depressive disorder (MDD) constitutes a main risk factor for suicide. Suicide risk in psychiatric patients is primarily determined by often unreliable, self-reported information. We assessed serum levels of three microRNAs, previously demonstrated to be dysregulated in post-mortem brain samples of suicide victims, as potential peripheral biomarkers for suicidality. Methods: All study participants were diagnosed with MDD according to Diagnostic and Statistical Manual of Mental Disorders, 5th edition criteria. Suicidality, defined as acute suicide risk or suicide attempt within one week prior to study entry, was assessed by clinical interview. Relative serum levels of miR-30a, miR-30e, and miR-200a, normalized to U6, were measured by quantitative real-time PCR in MDD inpatients with (MDD/SI, N=19) and without (MDD, N=31) acute suicide risk. Median age and gender distribution were comparable in both groups. Results: Levels of miR-30a, miR-30e, and miR-200a were significantly elevated in MDD/SI compared to MDD. Subgroup analysis of the MDD/SI group showed that levels of miR-30e and miR-200a were significantly higher and miR-30a was increased by trend in patients admitted following a suicide attempt (N=7) compared to patients with acute suicide risk but without recent suicide attempt (N=12). Additionally, use of two databases for in silico transcription factor–miRNA interaction prediction indicated early growth response protein (EGR)1 as potential transcriptional regulator for all three microRNAs. Conclusion: This study demonstrates suicide risk in MDD patients to be associated with increased levels of miR-30a, miR-30e, and miR-200a. Thus, these microRNAs might constitute potential biomarkers to predict suicidal behavior in MDD patients.